ACR–ACNM Practice Parameter for the Performance of Fluorine-18 Fluciclovine-PET/CT for Recurrent Prostate Cancer. (December 2018) - Savir-Baruch, Bital; Banks, Kevin P.; McConathy, Jonathan E.; Molchanova-Cook, Olga P.; Parent, Ephraim E.; Takalkar, Amol; Tulchinsky, Mark; Yu, Jian Q.; Subramaniam, Rathan M.; Schuster, David M.
Abstract : Abstract: The American College of Radiology (ACR) and American College of Nuclear Medicine (ACNM) collaborated to develop a clinical practice document for the performance of fluciclovine positron-emission tomography (PET) / computed tomography (CT) in the evaluation of patients with suspected prostate cancer recurrence based on the elevation of prostate-specific antigen (PSA) level (biochemical recurrence) after prior therapy. Prostate cancer is the third leading cause of cancer death in the United States. Up to 50% of patients diagnosed with prostate cancer will develop biochemical failure after initial therapy. The differentiation of local from extraprostatic recurrence plays a critical role in patient management. The use of functional imaging targeting features of cancer metabolism has proven highly useful in this regard. Amino acid transport is upregulated in prostate cancer. Fluciclovine ( anti -1-amino-3-F-18-fluorocyclobutane-1-carboxylic acid, FACBC, Axumin™) is an artificial amino acid PET tracer which demonstrates utility in the diagnosis of recurrent prostate cancer with significant added value to conventional imaging.